New species of Cercospora from North-eastern Uttar Pradesh - and A.K. SRIVASTAVA, R.K. SRIVASTAVA, S. NARAYAN (Indian Phytopathology, 2002)
Four new species of Cercospora, viz., C. adiniana, C. araliae, C. basellae-albae and C. cocculihirsuti, occurring on Adina co rdifolia, Aralia spinosa, BaseLla alba and Cocculus hirsutus respectively, are described and illustrated.